Acute kidney injury after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in patients with advanced ovarian cancer - Bai, Yun; Du, Ye; Ye, Pengpeng; Luo, Yang (Frontiers in Oncology, 2023)
Background Ovarian cancer is one of the most common gynecologic cancers with the highest mortality rate in China. Acute kidney injury (AKI) is a postoperative complication associated with all-cause mortality. The incidence and risk factors for AKI after cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) have not been fully elucidated. The purpose of this study was to determine the incidence and associate ed risk factors of AKI among those patients undergoing CRS-HIPEC. Methods This retrospective study collected demographic, tumor-related, preoperative, intraoperative, and postoperative data from 282 advanced ovarian cancer patients who underwent CRS-HIPECs. AKI was defined and staged according to the clinical practice guideline of Kidney Disease Improving Global Outcomes (KDIGO) in 2012. The prognosis of AKI was determined according to the change in serum creatinine 90 days after the operation. We conducted univariate and multivariate logistic regression analyses to assess the association between variables of interest and the occurrence of AKI. Results Of 282 advanced ovarian cancer patients, 11.7% of them developed AKI. The Multivariate logistic regression analysis showed that the risk factors independently associated with AKI included cisplatin dose≥70mg/m2 (OR=3.668, 95%CI 1.336-10.070, P=0.012); Baseline eGFR<60 mL/min/1.73 m2 (OR=2.704, 95%CI 1.373-5.322, P=0.004); and concomitant medications of angiotensin convert enzyme inhibitor or angiotensin receptor blocker (ACEI or ARB) (OR=3.122, 95%CI 1.545-14.892, P=0.039). Conclusion Our study demonstrates that the incidence of AKI after CRS plus cisplatin-based HIPEC is not uncommon among advanced ovarian cancer patients. Cisplatin overdose, baseline kidney dysfunction, and use of ACEI or ARB are independent risk factors for the occurrence of AKI among those patients.